Um estudo exploratório para o desenvolvimento da escala BBCC (benefícios buscados por consumidores de cinema) - Reis, Ana Beatriz Pereira (2019)
Cinema is part of the everyday life of most Brazilians as an entertainment option, so that the market is expanding and more and more have the opening of cinemas and movie sessions (ANCINE, 2018). Understanding the relevance of the film industry, this research aims to answer the following question: What are the benefits sought by movie consumers to go to theaters to watch movies? To answer this question, a scale as a metric instrument based on the benefits sought by cinema consumers was proposed and validated statistically up to the stage of exploratory analysis. The scale called BBCC (benefits sought by cinema consumers) aims to aid the literature of consumer behavior and allow new research on cinema consumption from this tool. The accomplishment of this work was done through two studies: Study 1 - qualitative and Study 2 - quantitative. Study 1 made focus groups to identify the construct constructs of segmented dimensions to be measured and explored by the scale. In this study, the following categories of benefits were obtained: rest, out-of-home activities, socialization, affection for films, watch a movie, environmental experience and affection for cinemas. Through the study of the benefits in Study 1, all the benefits found as variables of statistical analysis for Study 2 were used, aiming to understand which of these benefits were common among them for a segmentation and creation of significant factors for the formation of a more accurate scale and concise In order to do so, we conducted exploratory factor analyzes that identified two research groups, inspired by the findings of Cuadrado and Frasquet (1999) and Reis and Santana (2016): (i) And (ii) the Cinefilos. Within each of these groups were found the following factors: (i) Rest, Socialize and Disconnect, and (ii) Watch a Movie and Enjoy Cinema. Through these dimensions it was possible to restructure the benefits pointed out by Study 1 in similar groups and to understand the main needs of the sample reached (685 valid respondents). At first the proposed scale had 37 benefits scaled in 7 categories, after the analyzes have a proposal of scale of 28 benefits in 5 dimensions separated by two factors. It was applied to the 11-point Likert scale model allowing the respondent to choose 0 to 10 in relation to their identification with the construct. To test the reliability of this model, Cronbach's alpha was applied, and it was noted that all factors were approved: (i) Social: Leisure (Cronbach's alpha = 0.839), Disconnect (0.644), Socialize (0.644); (ii) Cinefilos: Watch a movie (0,688) and Likes the Environment (0,903). These are the benefits sought to be measured in the scale: stress, distraction, relaxation, fun, leisure, walking, general socialization, socialization with the family, escape from reality, isolation, specific film, film genre, film exclusivity, novelty movie quality, movie quality, movie quality, air conditioning, movie theatricality, movie theatricality, movie theatricality, movie theatricality, movie theaters, atmosphere, comfort, darkness, armchairs, audio quality, video quality, screen size. A bibliometric study of the academic productions between 1990 and 2018 was also carried out to identify the research gaps in this aspect, and it was noticed that there are few analyzes of the cinema market from an administrative and / or marketing point of view, being in Brazil a proposal for a better understanding of cinema consumer behavior. Therefore, this work contributes to the literature on consumer behavior, with a research tool and a segmentation proposal of the market for benefits; in addition to explaining the steps to create a scale according to Churchill (1979). In relation to management and society, this research contributes with material for assertive decision making and market strategies. It is suggested as main future research to develop a structured equation model of cause and effect between the dimensions and the factors, also relating the sociodemographic variables to better identify the possibilities of differentiated offers that the cinema can work.